2018
DOI: 10.1017/s0022109018000881
|View full text |Cite
|
Sign up to set email alerts
|

State Ownership and Debt Choice: Evidence from Privatization

Abstract: Using a large sample of privatized firms, we find that state ownership is significantly positively associated with the use of bank debt financing, suggesting that privatized firms benefit from the soft budget constraint associated with state ownership. We further find that the relation is more pronounced in countries with high government ownership of banks, high corruption in bank lending, a left-oriented government, and a collectivist national culture, which provides additional support for the soft-budget-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 91 publications
2
37
0
Order By: Relevance
“…State ownership allows companies to access long-term debt, and most likely with less collateral requirements. This result is consistent with the findings of Choi (2015) and Boubakri and Saffar (2017). However, the non-monotonicity of the SO variable suggests that the positive impact only exists when state ownership levels are less than 47 %.…”
Section: Non-linear Effects Of Ownership Structure Growth Opportunitsupporting
confidence: 91%
See 3 more Smart Citations
“…State ownership allows companies to access long-term debt, and most likely with less collateral requirements. This result is consistent with the findings of Choi (2015) and Boubakri and Saffar (2017). However, the non-monotonicity of the SO variable suggests that the positive impact only exists when state ownership levels are less than 47 %.…”
Section: Non-linear Effects Of Ownership Structure Growth Opportunitsupporting
confidence: 91%
“…Choi (2015) showed that State ownership has a positive and significant effect on corporate debt maturity in an empirical analysis of Chinese firms. Boubakri and Saffar (2017) corroborated these results in a study applied to firms from 62 countries, between 2001 and 2014, arguing that State ownership in companies makes requirements for access to debt financing more flexible. In Chile, there are no studies that analyze the effects of State ownership on debt maturity and therefore we established the following hypothesis:…”
Section: H1: Managerial Ownership Has a Non-linear Effect On Debt Matsupporting
confidence: 54%
See 2 more Smart Citations
“…We exploit recently available data on debt structure in Capital IQ to analyze the effect of political uncertainty stemming from national elections on the choice between public and bank debt. Most of prior studies on debt choice study the role of characteristics of the firm, like financial characteristics (e.g., Denis and Mihov, 2003), ownership structure (Lin, Ma, Malatesta and Xuan, 2013;Boubaker, et al, 2017;Boubakri and Saffar, 2018) and product market competition (e.g., Boubaker, Rouatbi and Sassi, 2018). We augment these studies by highlighting the importance of political uncertainty stemming from national elections for debt structure.…”
Section: Introductionmentioning
confidence: 99%